Opportunities of Artificial Intelligence for Enhancing the Sustainability of Community Adult Learning for National Development: Opportunities and Challenges - Abubakar, Umar Magaji; Wada, Idris Aujara (Kashere Journal of Education, 2025)
Artificial intelligence (AI) presents powerful opportunities for transforming adult community learning in Nigeria by improving access, personalising instruction, and supporting workforce development. As national development increasingly depends on digital competencies and lifelong learning, AI can help close literacy gaps, enhance employability skills, and promote inclusive participation in the knowledge economy. This position paper critically examines how AI can support the sustainability of community adult learning programmes in Nigeria, focusing on equitable access, digital skill advancement, and institutional strengthening. It explores opportunities such as intelligent tutoring, language translation tools, data-driven decision-making, and skills simulation technologies. At the same time, the paper analyses major challenges, including low AI awareness, inadequate infrastructure, funding limitations, digital inequality, and concerns about data ethics. Based on Human Capital Theory and the Technology Acceptance Model, the paper says that using AI in a smart and inclusive way is crucial for improving Nigeria’s human development, workforce productivity, and economic growth. It concludes with a call for coordinated policies, multi-stakeholder partnerships, investment in digital infrastructure, and capacity development for adult educators to ensure AI contributes to sustainable national development goals.